A conceptual framework of design and material process of kenaf fibre-based furniture manufacturing / Siti Nurul Diana Sukri … [et al.] - Sukri, Siti Nurul Diana; Shaharudin, Haszlin; Ahmad, Mohammad Azroll; Wan Omar, Wan Noor Faaizah (Universiti Teknologi MARA, 2018)
This paper presents a conceptual framework of using kenaf fibres-based as potential application materials for furniture design manufacturing in Malaysia. Kenaf or Hibiscus Cannabinus are currently used in various types of industrial applications to increase strength and to optimize weight and cost of the production. More specifically, this review has discovered that little has been published in the context of material process and design development on furniture design perspective. Isues relating to environmental threatened the life cycle of the environment globally due to the high-demanding export furniture design based on timber such as rubberwood. It has become a serious matter since the government’s introduced kenaf as alternative materials and there are deficiencies of collaboration and networking between scientist and designer to ensure the continuity in supports of research and development in Kenaf between government and manufacturer. Moreover, this conceptual framework study will purpose a guideline, solution and recommendations as potential materials through furniture design application for designer and manufacturer.